CONFLICT TO COLLABORATION: EFFECTIVE STRATEGIES FOR MANAGING WORKPLACE DYNAMICS - Marlissa Oktaviani; Ramon Zamora; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article addresses the persistent organizational challenge of workplace conflict, which, when mismanaged, leads to decreased morale, productivity loss, and talent attrition. The objective is to provide a practical framework for shifting conflict from a destructive force to a catalyst for collaboration and innovation. The methodology synthesizes contemporary research in organizational psychology, mediation principles, and leadership studies to construct a multi-tiered strategy encompassing leadership intervention, cultural systems, and individual skills. The results present a clear model for diagnosing conflict sources, a step-by-step facilitation process for leaders, and proactive systems for building a resilient team culture. The discussion emphasizes that effective management transforms conflict from an emotional drain into a strategic gain, fostering psychological safety and robust problem-solving. The conclusion asserts that mastering workplace dynamics is not an optional soft skill but a core leadership competency essential for building adaptable, high-performing teams.